Spatial Analysis to Mapping Homogeneous Units for Environmental Planning. Study Case Conservation Land Area, Mexico City, Mexico - Daniel, López L.; Aristides, Saavedra G. (European Journal of Applied Sciences, 2022)
In Mexico City, the territorial unit known as "conservation land" is of vital importance for the city since it provides essential environmental services for the quality of life of its inhabitants. In recent decades, the growth of the urban sprawl of Mexico City and its suburban area, as well as the advance and expansion of the agricultural frontier, have become the main threats to the proper functioning of the natural system, and therefore affect the environmental services they provide to the city. To provide elements for the territorial planning process, a project was carried out with the objective of evaluating the land suitability of the conservation land, as a basic input for a territorial management proposal, as a strategy for land use planning at regional level. The suitability evaluation was based on the Land Use Capability Classification system developed by the United States Soil Conservation Service, adapted by the authors for the conditions of the study area. The basic input for the management proposal is the evaluation of suitability, which is modeled and analyzed in conjunction with other databases, through structured queries in SQML language; the result is a management proposal in two levels, zones, and subzones. It is concluded that the biophysical land use planning proposed here is an option to address and solve the environmental problems in the study area, and that it can be used at different levels of government where land use policies are designed at different spatial scales. Geospatial modeling and analysis were key elements in the analysis and integration of the information.